Unions' perception toward changing landscape of industrial relations in Malaysia - Che Rose, Raduan; Samy, Naresh Kumar; Gani, Harris (Eurojournals, 2008)
This study examined the nature, extent, and scope of environmental changes faced by private sector employee unions in Malaysia. The elements in the environment of industrial relations system that been investigated are sectoral/industrial establishments, management strategies, workplace practices, and work environment. In a nutshell, this article provides an overview of the environmental trends and kind of strategies, policies, and support systems unions have put in place to facilitate workplace change that benefit membership, improve the work environment, and strengthen the union influence in the workplace.